Pengaruh Terpaan Tayangan Horor “Diary Misteri Sara” Pada Youtube Channel Sara Wijayanto Terhadap Sikap Kepercayaan Akan Mistis - Nurdianti, Khofifah; Basarah, Finy Fitrya (Neolectura, 2024)
YouTube is one of the most popular social media because it has various types of content that can be watched freely, including horror and mystical content. One of the YouTube channels who has horror content is